Study on interfacial shear characteristics and progressive failure model of geotextile bags - Hui Li; Miao Shi; Jia Zhang; Liangliang Peng (PLoS ONE, 2025)
Geotextile bag dams withstand the earth pressure of tailings in tailings reservoir by the shear stress on interface of geotextile bags. To improve the interfacial friction characteristics, pull-out tests were conducted on geotextile bags filled with fine tailings slurry containing various cement content, and the influences of cement content on the interfacial shear characteristics were explored. To describe the progressive failure of the interface, the theoretical analysis of interface pull-out behavior was performed. The results revealed that adding content cement into fine tailings slurry not only augmented the shear strength and residual strength ratio of the interface but also postponed interface softening. The optimal amount of cement was 3%, and the apparent friction angle which played a dominant role in interface strength was increased 17.4%, compared with no cement used. The elastic-plastic model and trilinear softening model were respectively improved to conform to the interfacial shear characteristics obtained in pull-out tests under low normal stress (< 60 kPa) and high normal stress (≥60 kPa). The interface shear stiffness of geotextile bag with the interfacial displacement within 20 mm and the dynamic compression modulus along the drawing direction were regarded as significant model parameters. The comparative analysis of shear stress-displacement curves, which were obtained from model calculating and test measuring, was carried out to verify the reliability and rationality of the model. The evolution patterns of the plastic zone, softening zone and residual zone of the interface were analyzed based on the model, and the warning values for interface failure were proposed. The development degree of interfacial plastic zone, softening zone and residual zone can be approximately calculated by quadratic polynomial of normalized pull-out force. The research results of this paper will provide reliable theoretical support for the design, construction and operation management of geotextile bag dams.